Economic Underpinnings of Early Marriage: The Tengka Tradition among the Madurese - Dikuraisyin, Basar; Sumarkan; Fatwa, Ah Fajruddin; Masadah (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
The minimum age for marriage has been established in Indonesian law. However, modern society in Madura often disregards these regulations. As a result, the phenomenon of early marriage remains prevalent among the society. Many researchers argue that early marriage is primarily influenced by cultural practices. However, this study identifies the occurrence of early marriage as being driven by the economic transactions embedded within marriage process. This economic aspect is referred to as the tengka tradition. This research examines the tengka tradition as an economic narrative underlying the resilience of early marriage in traditional Madurese society. Using a qualitative approach, data were collected descriptively through in-depth interviews with traditional leaders, religious figures (kiai), and individuals involved in underage marriages. The findings reveal that the resilience of early marriage is not primarily due to cultural or religious factors but is instead driven by the economic determination encapsulated in the tengka tradition. This economic determination manifests as asset accumulation through symbolic marriage transactions and as investment in the family’s future. The tengka tradition emerges as a significant factor that reshapes the ‘legal disobidience’ in the society, overshadowing elements such as religion and culture. It plays a crucial role in ensuring the social and economic stability of families and communities. [Usia minimum pernikahan telah diatur dalam undang-undang Indonesia. Namun, masyarakat modern di Madura sering mengabaikan peraturan tersebut. Akibatnya, fenomena pernikahan dini masih marak terjadi di masyarakat. Banyak peneliti berpendapat bahwa pernikahan dini dipengaruhi terutama oleh praktik budaya. Namun, penelitian ini mengidentifikasi terjadinya pernikahan dini sebagai akibat dari transaksi ekonomi yang sengaja dilestarikan dalam proses pernikahan. Aspek ekonomi ini dikenal dengan tradisi tengka. Penelitian ini mengkaji tradisi tengka sebagai narasi ekonomi yang mendorong terjadinya pernikahan dini dalam masyarakat Madura. Menggunakan pendekatan kualitatif, data dikumpulkan melalui wawancara mendalam dengan pemimpin tradisional, tokoh agama (kiai), dan individu yang terlibat dalam pernikahan di bawah umur. Hasil penelitian menunjukkan bahwa eksistensi pernikahan dini bukanlah semata-mata disebabkan oleh faktor budaya atau agama, melainkan dipengaruhi oleh praktik ekonomi yang terwujud dalam tradisi tengka. Faktor ekonomi ini bebentuk akumulasi aset melalui transaksi pernikahan simbolik dan sebagai investasi untuk masa depan keluarga. Tradisi tengka muncul sebagai faktor penting yang melestarikan ‘ketidakpatuhan hukum’ dalam masyarakat terkait batas minimum usia perkawinan, mengalahkan elemen-elemen seperti agama dan budaya. Tradisi ini dilakukan karena memainkan peran krusial dalam memastikan stabilitas ekonomi keluarga serta eksistensi dalam komunitas.]